Pathophysiology and epidemiology of virus-induced asthma - Akihide Ryo (Frontiers Research Topics, 2015)
Virus-caused asthma, we now call a phenotype of asthma. Regardless of the significance and popularity of this disease, the etiology of the virus-induced asthma have not well understood. In addition, a few effective vaccines have been applied to prevent respiratory virus infection. To solve the issues, it is essential to clarify and delineate both aspects of the virus and host defense systems including acute/chronic inflammation and airway tissue remodeling. To deeply review and discuss pathophysiology and epidemiology of virus-induced asthma, this topics includes new findings of the host immunity, pathology, epidemiology, and virology of asthma/chronic obstructive pulmonary disease (COPD). We believe that these works are well summarized and informative to glimpse the field of virus- associated asthma and COPD, and may help understanding the basic and clinical aspects of the diseases.